1992
DOI: 10.1063/1.462401
|View full text |Cite
|
Sign up to set email alerts
|

Negative-ion mass spectrometric study of ion-pair formation in the vacuum ultraviolet. VI. CH3X→X−+CH+3 (X=F, Cl, Br)

Abstract: Ion-pair formation from photoexcited halomethanes, CH3X*→X−+CH+3 (X=F, Cl, Br) has been studied by measuring photodissociation efficiency curves of X− using synchrotron radiation in the 9.9–27.5 eV photon energy range. A new spectral feature is observed in each of the curves near the threshold for the removal of an na1 electron from CH3X (n=4, 6, and 8, respectively, for CH3F, CH3Cl, and CH3Br ). This feature, composed of two or three peaks in each case, is interpreted as resulting from photoexcitation to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 19 publications
4
42
1
Order By: Relevance
“…Referring to the 2 2 E energy in CAS (9,6) at the neutral molecule geometry, the 2 A" minimum and the 2 A' lie at about 1.2-1.4 eV below the apex of the double cone, which corresponds to a much larger Jahn-Teller effect than for the CH 3 Br+ ( X 2 E) ground state (0.036 eV [2]). The 2 A' and 2 A" components geometries of the 2 2 E state are characterized by a larger C-Br bond (≈5%) but mostly by larger C-H bond lengths, either C-Hl ( 2 A' (CI)) or C-H2 ( 2 A" (min)) (see Table 6).…”
Section: (B))mentioning
confidence: 98%
See 1 more Smart Citation
“…Referring to the 2 2 E energy in CAS (9,6) at the neutral molecule geometry, the 2 A" minimum and the 2 A' lie at about 1.2-1.4 eV below the apex of the double cone, which corresponds to a much larger Jahn-Teller effect than for the CH 3 Br+ ( X 2 E) ground state (0.036 eV [2]). The 2 A' and 2 A" components geometries of the 2 2 E state are characterized by a larger C-Br bond (≈5%) but mostly by larger C-H bond lengths, either C-Hl ( 2 A' (CI)) or C-H2 ( 2 A" (min)) (see Table 6).…”
Section: (B))mentioning
confidence: 98%
“…In a negative-ion mass spectrometric study of the ion-pair formation, the production of X -ions has been investigated in the CH 3 X (X = F, CI, Br and I) molecules [6]. Owing to the lack of intensity of the photon beam in this experiment, no Br -ions have been detected below the 15 eV photon energy range.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the case of CH 3 Cl, it is a matter of debate as to whether one should use carbon-type Rydberg labels [22] or chlorine-type Rydberg labels [23]. These two labels yield n=3 and 4 for the low-lying Rydberg states, respectively.…”
mentioning
confidence: 99%
“…These data are available in the literature for CF 4 [41], SF 6 [42,43], CH 4 [44], CH 3 X (X = F, Cl, Br) [45], C 2 H 4 [46], C 2 H 6 [47,48], C 3 H 8 [47], and the chlorofluoromethanes (CFCl 3 , CF 2 Cl 2 , CF 3 Cl) [49]. The present work is in excellent agreement with these earlier studies and in most cases the quality and quantity of data obtained have improved.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Results have shown that in most cases, if charge transfer is energetically allowed, it will occur and is usually the dominant reaction channel [34][35][36][37][38][39][40][41][42][43][44][45]. The same experiments have shown that some cations and molecules do not react when the energetics do not allow for charge transfer.…”
Section: Cation-molecule Reactionsmentioning
confidence: 99%